Analyzing the Reasons for Formulating the Belt and Road Initiative - Wang, Kun (International Journal of Humanities and Education Development (IJHED), 2023)
The discussion over the impetus behind the Chinese government's actions in the realm of international relations has become more intense since the 1970s when China began the platform of reform and opening up. Based on The related literature, there are different kinds of opinions related to this issue. On the one hand, according to some academics, China's foreign policy is intended to showcase its tremendous might and begins with its own interests. According to particular academics, the foreign policy of the Chinese government focuses on cultural inclusiveness and takes social consensus as a central starting point. By using the example of the Belt and Road Initiative (BRI) to illustrate the variables influencing the formation of China's foreign policy, this study primarily examines the factors that influence foreign policy in China. Besides, the International relations (IR) theory and political heuristic theory will be used to carry out the discussion. The methodology of this paper will rely on secondary data to study the different views of the academic community and propose a foreign policy that China could adopt in the future.